THE INFLUENCE OF FINANCIAL CONFIDENCE, FINANCIAL SOCIALIZATION, HERDING, AND MENTAL ACCOUNTING ON INVESTMENT DECISION AMONG GENERATION Z IN JAKARTA - Angela, Della; Wiyanto, Hendra; Budiono, Herlina (Graduate Program of Universitas Tarumanagara, 2023)
This research purpose is to examine the influence of financial confidence, financial socialization, herding, and mental accounting on investment decision among Generation Z in Jakarta. The samples for this research are investors who were born between 1995-2010 (Generation Z) and living in Jakarta. The cluster sampling method was used to collect 205 respondents from a survey that was shared online on social media through google forms. The data of this research is analyzed through the use of a structural equation system using the SmartPLS.3.2.9 program. The result of this research shows that the investment decision of Gen Z investors in Jakarta is significantly influenced by financial confidence, financial socialization, herding, and mental accounting. This research also found that a lower frequency of trading which happens in Gen Z investors tends to overcome the negative impact of herding.